The world of power and energy - Ross, Frank Xavier, 1914- (Lothrop, Lee & Shepard Co., 1967)
Briefly surveys man's discovery and use of the several forms of power and energy, then details specific energy sources: sun, wind, water, fossil fuels, chemicals, and the atom.